Effects of Spirulina Platensis on hyperglycemia and mechanical allodynia in Streptazocin-induced diabetic rats: Spirulina Platensis on hyperglycemia and mechanical allodynia - Ghosh, Munmun; Tasnim, Syeda Fadia; Roy, Shuvajit; Ghash, Satabdi; Sathi, Meherun Nessa; Jahan, Nusrat; Mawa, Jannatul (Journal of the Medical College for Women & Hospital, 2024)
Background: Diabetic neuropathy is a serious complication of diabetes mellitus and exerts powerful pessimistic effect on patient’s life. This neuropathy induced pain is not relieved by taking usual analgesics. At present, several medicinal herbs have gained attention since these exhibit fewer side effects. In this regard, Spirulina platensis is one such herb that various activities beneficial to human health. Objective: To note the influence of oral Spirulina platensis (S.platensis) on hyperglycaemia and mechanical allodynia following its administration into Long Evans rats that have been induced into diabetic neuropathy. Materials and method: This research work was performed between March of 2017 and February of 2019 in the physiology department of BSMMU ( Bangabandhu Sheikh Mujib Medical University),Dhaka. Long Evan rats (12 in number, weighing 150-200g) were distributed in to 2 groups based on intervention. Group 1 was given oral Spirulina platensis, 400 mg/kg body weight while group 2 received normal saline 5ml/kg body weight once daily and here experiment performed was Von Frey test. The experiment was carried out for 21 days. Mean±SEM was used to express the data that was analyzed with SPSS (version 16.0). Comparison between the 2 groups was done by means of independent sample ‘t’ test and significance level was taken at p 0.05 . Results: In this study, Spirulina platensis demonstrated significant reduction in blood glucose level (p≤0.01) and higher paw withdrawal threshold (p 0.001) of diabetic rats in estimation of random blood glucose level and Von Frey test respectively. Conclusion: The present study concluded that, S. platenis attenuates hyperglycaemia and mechanical allodynia in rats with diabetic neuropathic pain. J Med Coll Women Hosp.2024;20(2): 56-63